Embryonic Stem Cells Cultured in Microfluidic Chambers Take Control of Their Fate by Producing Endogenous Signals Including LIF. (25th February 2016) - Guild, Joshua; Haque, Amranul; Gheibi, Pantea; Gao, Yandong; Son, Kyung Jin; Foster, Elena; Dumont, Sophie; Revzin, Alexander
Abstract: It is important to understand the role played by endogenous signals in shaping stem cell fate decisions to develop better culture systems and to improve understanding of development processes. In this study, we describe the behavior of mouse embryonic stem cells (mESCs) inside microfluidic chambers (microchambers) operated under conditions of minimal perfusion. mESCs inside microchambers formed colonies and expressed markers of pluripotency in the absence of feeders or pluripotency-inducing signals such as leukemia inhibitory factor (LIF), while mESCs in standard cultureware differentiated rapidly. In a series of experiments, we demonstrate that remarkable differences in stem cell phenotype are due to endogenous production of LIF and other growth factors brought upon by cultivation in confines of a microchamber in the absence of perfusion (dilution). At the protein level, mESCs produced ∼140 times more LIF inside microchambers than under standard culture conditions. In addition, we demonstrate that pluripotent phenotype of stem cells could be degraded by increasing the height (volume) of the microchamber. Furthermore, we show that inhibition of LIF in microchambers, via the JAK/STAT3 pathway, leads to preferential differentiation into mesoderm that is driven by bone morphogenetic protein (BMP)-4. Collectively, we demonstrate for the first time that it is possible to design a cell culture system where stem cell fate is controlled solely by the endogenous signals. Our study may help shift the paradigm of stem cell cultivation away from relying on expensive exogenous molecules such as growth factors and toward designing culture chambers for harnessing endogenous signals. Abstract : mESCs confined to small volume microfluidic chambers remain pluripotent in the absence of exogenous growth factors and feeder cell layers, whereas mESCs in standard (large volume) cultureware in the same media differentiate rapidly. We demonstrate that this is due to production and accumulation of endogenous growth factors enabled by microchamber culture. For example, in small volumes endogenous LIF reaches concentrations sufficient to control stem cell pluripotency via of activation of the JAK/STAT3 pathway.